Smart Charging and Renewable Grid Integration - A Case Study Based on Real-Data of the Island of Porto Santo - Strobel, Leo; Schlund, Jonas; Brandmeier, Veronika; Schreiber, Michael; Pruckner, Marco (Lecture Notes of the Institute for Computer Sciences, Social-Informatics and Telecommunications Engineering, LNICST, 2021)
The penetration of battery electric vehicles is increasing. Due to their ability to store electrical power and to shift charging events, they offer a wide range of opportunities with regard to renewable grid integration and lowering the overall CO2 emissions. This is particularly evident for isolated microgrids, such as the Portuguese island of Porto Santo. In this paper, we conduct a data analysis of real-world charging data of 20 electric vehicles operated on the island of Porto Santo. We provide insights into the charging behavior of different users and analyze the opportunity of smart charging for better renewable grid integration using linear optimization models. The data analysis shows that drivers prefer home rather than publicly available charging stations, flexible charging events occur mostly overnight and the charging flexibility of the fleet decreases over the project duration. With regard to make charging more flexible, we can see that smart charging can help to raise the share of electricity generated by renewable energy sources for charging the electric vehicles to up to 33%.
CRIS-Team Scopus Importer:2021-05-28
Keywords: Electric vehicles; Grid integration; Smart charging; Vehicle-2-Grid